The Neo-developmentalism Alternative : Capitalist crisis, popular movements, and economic development in Argentina since the 90s - Féliz, Mariano (2014)
Fil: Féliz, Mariano. Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación. Instituto de Investigaciones en Humanidades y Ciencias Sociales (UNLP-CONICET); Argentina.